Do Active Labor Market Policies Increase Employment? - Estevao, Marcello (Washington, D.C. : International Monetary Fund, 2003)
Using panel data for 15 industrial countries, active labor market policies (ALMPs) are shown to have raised employment rates in the business sector in the 1990s, after controlling for many institutions, country-specific effects, and economic variables. Among such policies, direct subsidies to job creation were the most effective. ALMPs also affected employment rates by reducing real wages below levels allowed by technological growth, changes in the unemployment rate, and institutional and other economic factors. However, part of this wage moderation may be linked to a composition effect because policies were targeted to low-paid individuals. Whether ALMPs are cost-effective from a budgetary perspective remains to be determined, but they are certainly not substitutes for comprehensive institutional reforms.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet